2009
DOI: 10.1016/j.jaci.2008.10.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel group of rhinoviruses is associated with asthma hospitalizations

Abstract: Overall, HRVCs were detected in 7% of children hospitalized for fever or respiratory conditions and constituted almost half of all rhinovirus-associated hospitalizations, suggesting that this novel group causes a substantial burden of pediatric disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
254
11
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(296 citation statements)
references
References 54 publications
28
254
11
3
Order By: Relevance
“…Interestingly, in the present pediatric study about 59.7% of picornaviruses infection cases are related to low respiratory tract infections (LRTIs) although these viruses are usually related to mild URTI. These results underline a need for picornaviruses investigation during viral diagnosis of respiratory tract diseases in light of recently published data regarding the association of rhinoviruses especially with severe respiratory tract infections in children [37][38][39], and in asthma exacerbations [16,[40][41][42].…”
Section: Authors' Contributionssupporting
confidence: 63%
“…Interestingly, in the present pediatric study about 59.7% of picornaviruses infection cases are related to low respiratory tract infections (LRTIs) although these viruses are usually related to mild URTI. These results underline a need for picornaviruses investigation during viral diagnosis of respiratory tract diseases in light of recently published data regarding the association of rhinoviruses especially with severe respiratory tract infections in children [37][38][39], and in asthma exacerbations [16,[40][41][42].…”
Section: Authors' Contributionssupporting
confidence: 63%
“…Indeed, the sequencing results do not reflect the full spectrum of HRV/HEV strains that may be circulating in ILI patients in Senegal, and may be biased toward samples with a high viral load; and especially for HRV, systematic type identification of positive samples would allow to pick up seasonal differences among the individual HRV species in Senegal, as reported in studies conducted in other geographical areas. [49][50][51] In conclusion, the results of the present study suggest strong year-round respiratory picornavirus activity in children up to 5 years of age in Senegal. Molecular studies identified a wide variety of RVs along with CBV in samples from patients with ILI.…”
Section: Discussionmentioning
confidence: 53%
“…Febrile wheeze and asthma exacerbation were the commonest presentation (76%) of RV-C infection, whereas others have shown strong associations of this novel RV with bronchitis, bronchiolitis and pneumonia [48,49]. In a prospective study of preschool children hospitalised with acute respiratory illness or fever, RV-C infections accounted for 46% of RV-positive samples and were significantly associated with an asthma diagnosis at hospital discharge compared to patients with RV-A (55 versus 36%, respectively) [50]. This result has now been duplicated in various settings, suggesting that this novel group might cause a substantial burden in paediatric asthma [51][52][53].…”
Section: Infection Among Factors Precipitating Asthma Exacerbationsmentioning
confidence: 97%